Teacher Strategies for Managing Reading Instruction for Slow Learners in Inclusive Elementary School Classrooms - Wiga Santri Rohinia; Asmara Yumarni; Meirita Sari (CV. Edujavare Publishing, 2026)
This study aims to describe the strategies employed by teachers to manage reading instruction for slow-learning students in inclusive elementary school classrooms. A qualitative, descriptive research approach was adopted. The study was conducted at SD Alam Mahira in Bengkulu City, involving the principal, a fourth-grade teacher, a shadow teacher, and slow-learning students as subjects. Data were collected through observation, interviews, and documentation, and subsequently analyzed using the interactive analysis model developed by Miles, Huberman, and Saldaña, which encompasses data condensation, data display, and conclusion drawing and verification. Data validity was ensured through technique and source triangulation. The findings indicate that the teachers' strategies for managing reading instruction involved a series of interconnected stages: identifying students' initial abilities; formulating adaptive lesson plans; conducting instruction using the phonics method; utilizing concrete and visual learning media; implementing inclusive classroom management; providing individual support; fostering collaboration with shadow teachers; and carrying out continuous learning evaluations. These strategies enabled reading instruction to be tailored to the characteristics and learning needs of slow-learning students, thereby allowing them to participate actively alongside regular students. The study demonstrates that the success of reading instruction in inclusive classrooms depends on the teacher's ability to integrate various instructional strategies in an adaptive manner that centers on the students' needs.